Who are the microenterprise owners? Evidence from Sri Lanka on Tokman v. de Soto - Suresh De Mel; David McKenzie; Christopher Woodruff (Institute for the Study of Labor (IZA), 2008)
Is the vast army of the self-employed in low income countries a source of employment generation? We use data from surveys in Sri Lanka to compare the characteristics of own account workers (non-employers) with wage workers and with owners of larger firms. We use a rich set of measures of background, ability, and attitudes, including lottery experiments measuring risk attitudes. Consistent with the ILOs views of the self employed (represented by Tokman), we find that 2/3rds to 3/4ths of the own account workers have characteristics which are more like wage workers than larger firm owners. This suggests the majority of the own account workers are unlikely to become employers. Using a two and a half year panel of enterprises, we show that the minority of own account workers who are more like larger firm owners are more likely to expand by adding paid employees. The analysis suggests that finance is not the sole constraint to growth of microenterprises, and provides an explanation for the low rates of growth of enterprises supported by microlending.
urn:nbn:de:101:1-2008060556
Keywords: O17; 330; Entrepreneurship; self-employment; De Soto; Unternehmer; Selbstständige; Persönlichkeitspsychologie; Risikopräferenz; Informeller Sektor; Mikrofinanzierung; Sri Lanka